Comparison of marmoset and human FSH using synthetic peptides of the β‐subunit L2 loop region and anti‐peptide antibodies. (June 2016) - Kutteyil, Susha S.; Kulkarni, Bhalchandra J.; Mojidra, Rahul; Joseph, Shaini; Pathak, Bhakti R.; Mahale, Smita D.
Abstract : Follicle stimulating hormone (FSH) is a glycoprotein hormone required for female and male gametogenesis in vertebrates. Common marmoset ( Callithrix jacchus ) is a New World primate monkey, used as animal model in biomedical research. Observations like, requirement of extremely high dose of human FSH in marmosets for superovulation compared to other primates and generation of antibodies in marmoset against human FSH after repeated superovulation cycles, point towards the possibility that FSH–FSH receptor (FSHR) interaction in marmosets might be different than in the humans. In this study we attempted to understand some of these structural differences using FSH peptides and anti‐peptide antibody approach. Based on sequence alignment, in silico modeling and docking studies, L2 loop of FSH β‐subunit (L2β) was found to be different between marmoset and human. Hence, peptides corresponding to region 32–50 of marmoset and human L2β loop were synthesized, purified and characterized. The peptides displayed dissimilarity in terms of molecular mass, predicted isoelectric point, predicted charge and in the ability to inhibit hormone–receptor interaction. Polyclonal antibodies generated against both the peptides were found to exhibit specific binding for the corresponding peptide and parent FSH in ELISA and Western blotting respectively and exhibited negligible reactivity to cross‐species peptide and FSH in ELISA. The anti‐peptide antibody against marmoset FSH was also able to detect native FSH in marmoset plasma samples and pituitary sections. In summary, the L2β loop of marmoset and human FSH has distinct receptor interaction ability and immunoreactivity indicating possibility of subtle conformational and biochemical differences between the two regions which may affect the FSH–FSHR interaction in these two primates. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Marmoset and human FSH L2β loop regions show dissimilar interactions with cognate FSHR in in silico docking studies. The marmoset and human FSHβ (32–50) peptides corresponding to L2β loop exhibit differential biochemical properties including in vitro receptor interaction ability. The marmoset and human FSH 32–50 region of L2β loop also exhibit differential immunoreactivity indicating possibility of dissimilarities in the conformational and biochemical properties of the two regions.